Pork Tapeworm (Taenia Saginata Asiatica) Infection in Rural Bangladesh - Amin, Md Robed; Rabbi, Shekh Fazle; Zaman, Md Ferdous; Rahman, Md Khalilur (Journal of Medicine, 2009)
Tapeworm infection is most common in cattle and pork breeding areas. Humans are the definitive host. Gravid segments of T saginata are passed in human feces to soil, where they are ingested by grazing animals, especially cattle. The eggs then hatch to release embryos that encyst in muscle as cysticerci. Humans are infected by eating raw or undercooked infected beef. Most individuals infected with T saginata are asymptomatic, but abdominal pain and other gastrointestinal symptoms may be present. Eosinophilia is common. The most common presenting finding is the passage of proglottids in the stool. Treatment is highly satisfactory with praziquantel. Taenia Saginata Asiatica is a variant of Taenia saginata where the intermediate host is Pork. Normally the pork tapeworm is mean for Taenia solium. But in case of asiatica variant it is Taenia Saginata that can also lead to pork tapeworm infection. It is not uncommon in south east asia region. Here is a case report of pork tapeworm in a primary are hospital in Bangladesh Key words: Pork, Tapeworm, Taenia Saginata Asiatica, Rural doi: 10.3329/jom.v10i2.2832 J MEDICINE 2009; 10 : 135-138